ANALISIS PENYEBAB KETERLAMBATAN STOK BAHAN KEMASAN MENGGUNAKAN METODE LEAN SUPPLY CHAIN MANAGEMENT (LSCM) PADA PT. XYZ - Nanda Ilfina Maulya; Indro Kirono (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to identify the causes of delays in packaging material stock at PT XYZ, which lead to production downtime and imbalance between critical and excess inventory. A qualitative case study approach was applied using interviews, observations, and documentation. Data were analyzed through the Lean Supply Chain Management (LSCM) framework and the DMAIC methodology, while the Fishbone Diagram was used to determine root causes. The results indicate two major forms of waste: waiting waste arising from manual PR and PO approvals, and inventory waste due to the absence of safety stock and non–real-time inventory updates. These issues stem from limited human resources, manual processes, and weak information flow. The study recommends digitalizing procurement processes and improving inventory control and coordination.